Lack of Generalization of Auditory Learning in Typically Developing Children. - Halliday, Lorna F.; Taylor, Jenny L.; Millward, Kerri E.; Moore, David R. (Journal of Speech, Language & Hearing Research, 2012)
Purpose: To understand the components of auditory learning in typically developing children by assessing generalization across stimuli, across modalities (i.e., hearing, vision), and to higher level language tasks. Method: Eighty-six 8- to 10-year-old typically developing children were quasi-randomly assigned to 4 groups. Three of the groups received twelve 30-min training sessions on multiple standards using either an auditory frequency discrimination task (AFD group), auditory phonetic discrimination task (PD group), or visual frequency discrimination task (VFD group) over 4 weeks. The 4th group, which was the no-intervention control (NI) group, did not receive any training. Thresholds on all tasks (AFD, PD, and VFD) were assessed immediately before and after training, along with performance on a battery of language assessments. Results: Relative to the other groups, both the AFD group and the PD group, but not the VFD group, showed significant learning on the stimuli upon which they were trained. However, in those instances where learning was observed, it did not generalize to the nontrained stimuli or to the language assessments. Conclusions: Nonspeech (AFD) or speech (PD) discrimination training can lead to auditory learning in typically developing children of this age range. However, this learning does not always generalize across stimuli or tasks, across modalities, or to higher level measures of language ability.